Plato dan Media Sosial: Etika, Pengetahuan, dan Tanggung Jawab dalam Penyebaran Informasi - Andzani, Diva; Sitorus, Fitzerald Kennedy (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2023)
The main focus of this study is on the analysis of classical philosophy concepts, particularly the works of Plato. Its aim is to investigate and analyze Plato's thoughts on the aspects of ethics, knowledge, and responsibility in the context of digital communication. From the research findings, it is evident that Plato's ideas still hold significant relevance in addressing challenges in the era of social media. The application of Plato's ethics, especially concerning objective truth and justice, becomes a crucial key in managing information in the complex digital age. This study also highlights the importance of critical thinking skills, understanding Plato's concepts of eternal knowledge, and media literacy as essential foundations to confront the complexity of information. In conclusion, this study affirms that Plato's ideas have provided a solid foundation in shaping a more ethical and wise digital ecosystem.